Digital PCR-based genetic profiling from vitreous fluid as liquid biopsy for primary uveal melanoma: a proof-of-concept study - R. J. Nell; M. Versluis; N. V. Menger; M. C. Gelmi; T. H.K. Vu; R. M. Verdijk; G. P.M. Luyten; M. J. Jager; P. A. van der Velden (Journal of Experimental & Clinical Cancer Research)
Abstract Background Uveal melanoma is an aggressive ocular malignancy. Early molecular characterisation of primary tumours is crucial to identify those at risk of metastatic dissemination. Although tumour biopsies are being taken, liquid biopsies of ocular fluids may form a less invasive but relatively unexplored alternative. In this study, we aim to evaluate the DNA content of vitreous fluid from eyes with a uveal melanoma to obtain molecular tumour information. Methods DNA was isolated from 65 vitreous fluid samples from enucleated eyes with a uveal melanoma and studied using digital PCR. Primary and additional driver mutations (in GNAQ, GNA11, PLCB4, CYSLTR2, BAP1, SF3B1 and EIF1AX) were investigated using accustomed targeted and drop-off assays. The copy numbers of chromosome 3p and 8q were measured using multiplex and single-nucleotide polymorphism-based assays. Our findings were compared to the molecular profile of matched primary tumours and to the clinicopathological tumour characteristics. Results Almost all (63/65) vitreous fluids had measurable levels of DNA, but melanoma-cell derived DNA (containing the primary driver mutation) was detected in 45/65 samples (median proportion 15.5%, range 0.03-94.4%) and was associated with a larger tumour prominence, but not with any of the molecular tumour subtypes. Among the vitreous fluids with melanoma-cell derived DNA, not all samples harboured (analysable) other mutations or had sufficient statistical power to measure copy numbers. Still, additional mutations in BAP1, SF3B1 and EIF1AX were detected in 15/17 samples and chromosome 3p and 8q copy numbers matched the primary tumour in 19/21 and 18/20 samples, respectively. Collectively, a clinically-relevant molecular classification of the primary tumour could be inferred from 29/65 vitreous fluids. Conclusions This proof-of-concept study shows that substantial amounts of DNA could be detected in vitreous fluids from uveal melanoma patients, including melanoma-cell derived DNA in 69% of the samples. Prognostically-relevant genetic alterations of the primary tumour could be identified in 45% of the patients. A follow-up study is needed to evaluate our approach in a prospective clinical context. Additionally, our work highlights improved possibilities to sensitively analyse scarce and heterogeneous tumour biopsies, with potential application in other malignancies.